Brug af kontanter i Danmark - Maria Carlsen; Johanne Dinesen Riishøj (Danmarks Nationalbank, 2006)
– The Working Paper analyses the use of cash in Denmark since 1990 and compares with the development in other EU-countries. The retail cash payments have decreased in the last 10 years, but cash still make up a significant part of the total retail sales. About half of the cash outstanding is held by households for registered transactions, by financial institutions, other companies, public authorities etc. The remaining part of the cash outstanding is supposed to be used for saving or other non-registered purposes. Cash usage in Denmark is approximately the same as in the UK but is lower than the use of cash in the Euro Area.
Keywords: 330